2016
DOI: 10.1093/cercor/bhw351
|View full text |Cite
|
Sign up to set email alerts
|

Primate Ventromedial Prefrontal Cortex Neurons Continuously Encode the Willingness to Engage in Reward-Directed Behavior

Abstract: To survive in their complex environment, primates must integrate information over time and adjust their actions beyond immediate events. The underlying neurobiological processes, however, remain unclear. Here, we assessed the contribution of the ventromedial prefrontal cortex (VMPFC), a brain region important for value-based decision-making. We recorded single VMPFC neurons in monkeys performing a task where obtaining fluid rewards required squeezing a grip. The willingness to perform the action was modulated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…Such findings, that sensations of fatigue were fluctuating in the experiment and could be quantified using the same computational model in which effort exerted causes changes in fatigue, suggest that changes to choice behaviour in the fMRI experiment are more likely to be due to exerted effort than accrued reward. In line with this, the UF and RF components fluctuated in regions that have previously been linked to effort processing, rather than in regions that have been found to signal accumulated reward 61 , 62 . Future work will need to identify the source of these fluctuating, putative fatigue states, and fully disentangle them from other processes, such as opportunity cost processing, boredom, task switching and time-on-task.…”
Section: Discussionsupporting
confidence: 63%
“…Such findings, that sensations of fatigue were fluctuating in the experiment and could be quantified using the same computational model in which effort exerted causes changes in fatigue, suggest that changes to choice behaviour in the fMRI experiment are more likely to be due to exerted effort than accrued reward. In line with this, the UF and RF components fluctuated in regions that have previously been linked to effort processing, rather than in regions that have been found to signal accumulated reward 61 , 62 . Future work will need to identify the source of these fluctuating, putative fatigue states, and fully disentangle them from other processes, such as opportunity cost processing, boredom, task switching and time-on-task.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast to costs such as delay or probability, effort is much more closely aligned with action systems. Indeed, several studies have shown that the evaluation of effort costs involve cortical–striatal circuits closely related to response selection, such as dorsomedial frontal cortex (anterior cingulate and supplementary motor cortex) and dorsal striatum/putamen 42 , 43 , 44 , 45 , 46 , 47 , 48 , and not circuits centered on orbital and ventromedial prefrontal cortices and parts of ventral striatum, which are more commonly implicated in benefits-based decisions (e.g., 49 , 50 ). Therefore, decisions relying on a cost–benefit analysis would result from a joint influence of these two systems on motor output.…”
Section: What Role Might Rapid Changes In Dopamine Play In Effort-relmentioning
confidence: 99%
“…However, in situations in which other variables influenced action tendencies, the vmPFC would best be viewed as coding for an action integration signal which would be distinct from a value signal (since it would include the influence of contextual variables). Consistent with this view, evidence implicates the vmPFC in an integrative role that includes value related factors such as reward, as well as contextual factors such as recent behavior and fatigue (San-Galli, Varazzani, Abitbol, Pessiglione, & Bouret, 2018).…”
Section: Discussionmentioning
confidence: 91%